The Institutionalisation of Participatory Singing since the 1960s in Estonia - Särg, Taive (Traditiones, 2023)
Previous research into the social structure of participatory singing indicates its decline within modern society (e.g. Blacking 1973, Turino 2008). The present study focuses on processes in amateur singing in Estonia using the “Music in my Life” questionnaire (2022). The results show the dynamics of contemporary participatory singing, which can be characterised as institutionalisation within the context of modern society.